TEXTBOOK AND METHODICAL STRUCTURE OF SOME PARAGRAPHS - Yakubova Gulnozaxon Taxirdjanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Lessons and paragraphs are practical methods used to explain content, teach, and convey information. The main purpose of this methodological structure is to teach students to explain information, express their opinions, make logical connections and analyze Lessons and paragraphs are practical methods used to explain content, teach, and convey information. The main purpose of this methodological structure is to teach students to explain information, express their opinions, make logical connections and analyze.